Ethical Leadership in HRM: Promoting Integrity and Trust in Organizational Practices - Sofyan, Ade; Susanto, Heri (Management Studies and Business Journal (PRODUCTIVITY), 2024)
This research explores the important role of ethical leadership in the context of human resource management (HRM) and its impact on organizational and employee behavior. Through a systematic analysis of the literature, we found that ethical leadership has a positive correlation with various leadership dimensions, such as transformational and transactional, and has a positive impact on job satisfaction and pro-environmental behavior. In addition, ethical leadership practices also influence organizational culture by promoting ethical norms and behavior that is consistent with ethical values. However, this research also identified that unethical organizational practices, particularly unethical organizational behavior (UPB), can have a significant negative impact on employees and the organization as a whole. We highlight the importance of leadership responsibility, organizational identification, and perceptions of corporate social responsibility (CSR) in influencing employee ethical behavior and its impact on the organization. Through this research, we propose strategies to mitigate the negative impact of unethical organizational practices through the implementation of ethical leadership in HRM.